A novel O-linked glycan modulates Campylobacter jejuni major outer membrane protein-mediated adhesion to human histo-blood group antigens and chicken colonization - Mahdavi, Jafar; Pirinccioglu, Necmettin; Oldfield, Neil J.; Carlsohn, Elisabet; Stoof, Jeroen; Aslam, Akhmed; Self, Tim; Cawthraw, Shaun A.; Petrovska, Liljana; Colborne, Natalie; Sihlbom, Carina; Boren, Thomas; et al. (Royal Society, 2014)
Campylobacter jejuni is an important cause of human foodborne gastroenteritis; strategies to prevent infection are hampered by a poor understanding of the complex interactions between host and pathogen. Previous work showed that C. jejuni could bind human histo-blood group antigens (BgAgs) in vitro and that BgAgs could inhibit the binding of C. jejuni to human intestinal mucosa ex vivo. Here, the major flagella subunit protein (FlaA) and the major outer membrane protein (MOMP) were identified as BgAg-binding adhesins in C. jejuni NCTC11168. Significantly, the MOMP was shown to be O-glycosylated at Thr268; previously only flagellin proteins were known to be O-glycosylated in C. jejuni. Substitution of MOMP Thr268 led to significantly reduced binding to BgAgs. The O-glycan moiety was characterized as Gal(β1–3)-GalNAc(β1–4)-GalNAc(β1–4)-GalNAcα1-Thr268; modelling suggested that O-glycosylation has a notable effect on the conformation of MOMP and this modulates BgAg-binding capacity. Glycosylation of MOMP at Thr268 promoted cell-to-cell binding, biofilm formation and adhesion to Caco-2 cells, and was required for the optimal colonization of chickens by C. jejuni, confirming the significance of this O-glycosylation in pathogenesis.